Visualization of Crime News Sentiment in Facebook - Bakri C. Haron, M.; Z. Z. Abidin, Siti; Azmina M. Zamani, N.; ., . (International Journal of Engineering and Technology, 2018)
Facebook has become a popular platform in communicating information. People can express their opinions using texts, symbols, pictures and emoticons via Facebook posts and comments. These expressions allow sentiment analysis to be performed by collecting the data to obtain the publicâ€™s opinions and emotions toward certain issues. Due to a huge amount of data obtained from Facebook, proper approaches are required to cater the texts and symbols used in the comments. There are also limited amount of dictionary on Malay texts which make it more challenging to process and classify the positive and negative words used in the comments. Thus, hybrid approach is applied during the data processing to visualize the results. In this work, a combination of lexicon-based approach and NaÃ¯ve Bayes are used. This study focuses on analyzing the publicâ€™s sentiments on crime news in Facebook by using word cloud visualization. The visualization displays important words used in a form of a word cloud. Moreover, the percentage of positive and negative words existed in the comments is also shown as part of the visualization results.Â